2013
DOI: 10.1111/iwj.12034
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stem cell attenuates skin fibrosis development in mice

Abstract: marrow-derived mesenchymal stem cell attenuates skin fibrosis development in mice. Int Wound J 2014; 11:701-710 Abstract Recent studies showed that mesenchymal stem cell (MSC) transplantation significantly alleviated tissue fibrosis; however, little is known about the efficacy on attenuating cutaneous scar formation. In this study, we established a dermal fibrosis model induced by bleomycin and evaluated the benefit of bone marrow-derived mesenchymal stem cells (BM-MSCs) on skin fibrosis development. Traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 37 publications
5
102
0
Order By: Relevance
“…In the case of wound healing, uMSCs attenuate tissue damage, inhibit fibrotic remodeling and apoptosis, promote angiogenesis, stimulate endogenous stem cell recruitment and proliferation, and reduce immune responses. However, the prevalent hypothesis has shown that, when used in cell-based therapy, uMSCs mainly provide benefits for wound healing via paracrine mechanisms [18,32]. Despite the early accumulation of systemically administered uMSCs at the site of injury, few uMSCs become permanently engrafted within the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of wound healing, uMSCs attenuate tissue damage, inhibit fibrotic remodeling and apoptosis, promote angiogenesis, stimulate endogenous stem cell recruitment and proliferation, and reduce immune responses. However, the prevalent hypothesis has shown that, when used in cell-based therapy, uMSCs mainly provide benefits for wound healing via paracrine mechanisms [18,32]. Despite the early accumulation of systemically administered uMSCs at the site of injury, few uMSCs become permanently engrafted within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…With the recognition that transplanted MSCs are not retained in organs for longer periods [18][19][20] (supplemental online Fig. 1A), we then suggested that their paracrine ability might play a key role in exerting their functions in promoting wound repair.…”
Section: Umsc-exos Suppress Myofibroblast Aggregation and Scar Formatmentioning
confidence: 97%
“…7 Present reports show that MSCs can decrease fibrosis in a mouse model. 117 Systemic therapies aimed at global immune suppression can improve the healing process, but the quality of healing may be compromised through a weakened scar formation. It is possible that MSCs can sense the degree of inflammation in the microenvironment and respond by releasing of growth factors, cytokines, and other mediators to reduce inflammation using real-time biochemical cues.…”
Section: Mscs: Mechanism(s) Of Actionmentioning
confidence: 99%
“…Ultimately, reduced scar formation is not an outcome desired specifically for chronic wounds, but nevertheless is a significant potential benefit of utilizing MSCs to promote closure of such non-healing wounds. Experimentally, recent experimental evidence has shown that MSCs can indeed reduce a fibrotic phenotype in a mouse model, 93 showing promise for reduced scar formation in future MSC therapeutics.…”
Section: Reduction In Scar Formationmentioning
confidence: 99%